Scrutinizing polarisation patterns and consequences of occupational transformation in the swedish labour market - Berglund, Tomas 1956-; Eriksson, Ylva Ulfsdotter (Routledge, 2024)
1. Scrutinizing Polarization: An Introduction Tomas Berglund and Ylva Ulfsdotter Eriksson2. The Transformation of the Swedish Labour Market: A Background Tomas Berglund3. The Transformation of the Occupational Structure in Sweden Tomas Berglund4. Occupational Prestige and Gendered Polarization Ylva Ulfsdotter Eriksson and Erica Nordlander 5. Polarized Perceptions of Occupational Prestige Ylva Ulfsdotter Eriksson 6. A Double Ethnic Penalty? The Mobility Patterns of Early Careers and Second-Generation Migrant Descent in Sweden Gabriella Elgenius, Denis Frank, Vedran Omanov©Ưc, and Tomas Berglund7. Polarization and Dualization in Digitalized and Flexible Companies Anna Hedenus and Erica Nordlander8. Platform WorkKristin Jesnes and Sophie Banasiak9. Work Environment Trajectories and Consequences for Trends of Sick Leave and Occupational Disorders Lotta Dellve, Linda Corin, and Gunnel Hensing 10. Changes in Trade Union Membership and Attitudes to Unions in Sweden Jesper Prytz and Bengt Larsson11. The Significance of Labour Market Changes on Wage and Income Inequality Tomas Berglund12. ConclusionsTomas Berglund and Ylva Ulfsdotter Eriksson
Keywords: Polarization (Social sciences) / Sweden; Equality / Sweden; Social groups / Sweden; Social change / Sweden; Labor market / Social aspects / Sweden; POLITICAL SCIENCE / Labor & Industrial Relations